Notes about ultrastructural testicular change in mice induced by the venom of southamerican mapanare snake (Bothrops colombiensis Hallowell, 1845) - Zárraga, Alexis; Velásquez, Luisa; Strauss, Miriam; Rodríguez Acosta, Alexis (Revista Científica de la Facultad de Ciencias Veterinarias, 1970)
In Venezuela, Bothrops colombiensis is responsible for about 80% of the bites by venomous snakes. The aim of this study was to determine the testicular ultrastructural changes produced by the toxic aggression of Bothrops colombiensis venom. Ten mice were inoculated intramuscularly with crude venom (2.5 mg /kg weight). Groups of 5 mice were sacrificed at 1 and 48 hours after venom inoculation (the control group was inoculated with saline solution). Samples of testicular tissue were extracted and immediately fixed by routine procedures and then processed for observation in a Hitachi H-300 transmission electron microscope. Ultrastructural changes in testicular tissue showed mitochondria changes of Sertoli cells, acrosomal membranes of the spermatids, and spermatozoids in their different stages. Comparing mitochondria from exposed animals versus control group oedematous mitochondria with lysis of the cristae, presenting a poor electronics density were evidenced. Mitochondria were inserted in a cellular debris environment. Lesions of the acrosomes were characterized by alterations of the external acrosomal membrane, intense separation of the internal acrosomal membrane and nuclear band, severe alterations at sperm tail level, characterized by a large submembranal space in contrast with controls, where the close vicinity between the membrane and mitochondria of the tail of spermatide was evident. The mitochondrial swelling in other biological systems is related to an ionic deregulation (CaÂ²+), which in this particular case could be assumed that the venom interact with the membrane, altering architecture and losing function as barrier. Â